Climate change mitigation and agriculture: measures, costs and policies – A literature review - Ollikainen, Markku; Lankoski, Jussi; Lötjönen , Sanna (Agricultural and Food Science, 2020)
We review the literature on climate change mitigation in agriculture with a focus on the use of climate policy instruments to incentivize the adoption of greenhouse gas mitigation measures. We develop an economic model characterizing the production decisions in animal and crop production farms and link our discussion on policy instruments to them. We review mitigation measures and their cost-effectiveness in reducing emissions. Given the multiple sources of agricultural emissions, the literature finds carbon taxes and emissions trading to perform best. The challenges involved in measuring and verifying changes in emissions make the implementation of policies targeting all sources of emissions difficult. Second-best policies addressing a subset of emissions, such as those from ruminants or mineral fertilizers, are more feasible but less efficient. Carbon sequestration in arable soils, while technically promising, faces the problems of heterogeneity in sequestration capacity, measurement, verification and permanence of sequestration. The variation of estimates on emissions reduction, abatement costs and differences in model simulations is large. A better basis for policy designs is needed.
Keywords: GHG emissions; carbon sinks; enteric fermentation; carbon tax; emissions trading; abatement subsidy